Accounting as a Normalizing Tool for Transitional Dirtiness: The Case of theUS Adult‐UseCannabis Industry* - Romi, Andrea M.; Carrasco, Heather; Camors, Casey A.; Masselli, John J. (Contemporary Accounting Research, 2022)
ABSTRACT While prior accounting research documents normalizing strategies within the accounting profession and in instances of accounting adoption, the potential of accounting itself as a strategic tool toward normalizing that which is considered socially abnormal (i.e., dirty) remains an important and unexamined area of inquiry. In this study, we conduct in‐depth interviews to examine the role accounting plays in the development of the US cannabis industry (CI) as it transitions from the illicit market in which formal accounting was systematically avoided to a state‐legal market in which participants are subject to conventional business processes. Facing impediments to traditional operating practices and pressures to increase normative conformity for industry survival, cannabis operators (COs) incorporated the use of accounting in three normalizing strategies (creative concession, collaborative facilitation, and experimentation), seemingly influenced by the incongruencies between prior illicit‐market culture and experiences and the state‐legal operating environment. In response to what operators perceived to be coercive regulation, they employed creative concession strategies, including influencing, bargaining, challenging, escaping, and cessation tactics. However, in response to pressures to adopt more commonly accepted forms of accounting, COs instead deployed two different strategies, one focused on acquiescence to normalizing pressures when doing so facilitated essential relationship building (i.e., collaborative facilitation strategies), and one deployed as strategic experimentation, working to normalize industry activities in areas of perceived threats to industry acceptance and continuity. Given CO accounting naiveté, its usefulness was often introduced by peripheral industry parties attempting to normalize their own participation with the CI. Notably, we also find that normalizing pressures occasionally resulted in unintended consequences, including reversion to the illicit market and forgoing normalizing strategies in favor of retaining some level of dirtiness to fend off pending competition, both of which threaten to reemphasize the industry's dirtiness. Our study, therefore, points to accounting itself as a central mechanism in the complex, multidirectional strategy to normalize transitional dirtiness.